Pentingnya Pendampingan Pastoral Pasca Dukacita terhadap Keluarga yang Kehilangan Karena Covid 19 - Siregar, Risma (JURNAL DIAKONIA, 2023)
Post-grief is a human reaction to defend oneself when facing loss events such as death, separation, or the loss of something valuable that affects aspects of human life holistically. Families who have lost due to Covid 19 which has caused life instability and has affected the holistic aspects including physical, social, mental and spiritual. This study aims to determine the grief experienced by families who lost because of Covid 19 in the aftermath of the HKBP Balige congregation. The grief experienced by families who have lost because of Covid 19 makes the family helpless and down because of a lack of social support. So it is necessary to support faith in the family in everyday life. Post-grief pastoral assistance provided by the HKBP Balige Church can restore families who have lost due to Covid 19.